Preparation of a palladium-supported highly crystalline carbon nitride and its application in catalytic dehydrogenation of dipentene
By preparing palladium-supported high-crystalline carbon nitride catalysts, the problems of low catalytic efficiency, selectivity and poor stability of traditional catalysts are solved, and efficient dipentene dehydrogenation preparation has good stability and recovery properties for umbrella hydrocarbons.
Patent Information
- Application Number
- CN202310651336.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-06-02
AI Technical Summary
The traditional catalytic dehydrogenation preparation of dipentene has problems such as low catalytic efficiency and selectivity, poor stability, difficulty in recycling, and environmental pollution, which restricts its application.
High crystalline carbon nitride was prepared by calcining the nitrogen-containing precursor and mixing it with alkali metal halide salt, calcining and grinding, and then supporting metal palladium by chemical reduction method to prepare a palladium-supported high crystalline carbon nitride catalyst.
The prepared palladium-supported high-crystalline carbon nitride catalyst has high activity, good stability, easy recovery and functionalization, and can effectively promote the dipentene dehydrogenation reaction. The content of the dipentene hydrocarbon in the product reaches 89.74%, and the dipentene conversion rate and selectivity for the dipentene hydrocarbon are close to 100%.
Smart Images

Figure CN116689010B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of palladium-supported high-crystalline carbon nitride and application thereof in the catalytic dehydrogenation of dipentene, belonging to the field of catalyst preparation and the technical field of preparing p-cymene by dehydrogenating dipentene. Background Art
[0002] Dipentene is a large amount of byproduct produced in the industrial process of synthesizing terpineol and camphor from turpentine oil. It is a renewable resource with a wide source and low price. Para-cymene is an important intermediate in fine chemical synthesis and has broad application prospects in pesticides, medicines, and synthetic materials. Catalytic dehydrogenation of dipentene to prepare para-cymene is one of the most ideal ways to produce para-cymene in the chemical industry. The para-cymene prepared by this method basically does not contain ortho- and meta-isomers, which overcomes the limitation of raw materials and the difficulty of separating products, and reduces the demand and dependence on fossil raw materials.
[0003] There are usually two methods for synthesizing p-cymene by catalytic dehydrogenation of dipentene: gas phase method and liquid phase method. The gas phase method has been industrialized abroad. The dehydrogenation catalyst used is mainly a catalyst loaded with precious metals such as Pd and Pt, and the yield is above 80%. However, the catalyst used in this process is very expensive and the production cost is high (Applied Catalysis A, 1999, 188 (1-2): 287). In China, the catalysts used for gas phase dehydrogenation mainly include Cr2O3-Al2O3, CuO-CrO3-Al2O3, 0.5% Pd-C, etc. (Applied Catalysis A, 1997, 158 (1-2): 145; Chemistry and Industry of Forest Products, 1993, 13 (4): 305). There are also some literature reports on catalysts used for liquid phase reactions, such as 5% Pd-impregnated activated carbon, Raney-Ni, nickel formate (the content of p-cymene obtained is 81%), etc. However, traditional catalysts have problems such as low catalytic efficiency and selectivity, poor stability, difficulty in recovery, and environmental pollution, which restrict their application in the catalytic dehydrogenation of dipentene to prepare p-cymene.
[0004] As people's awareness of environmental protection and energy conservation increases, the development and design of highly active, stable, easily recyclable and environmentally friendly supported heterogeneous catalysts has become the focus of research on the catalytic dehydrogenation of dipentene to prepare p-cymene. In recent years, a carbon nitride polymer mainly composed of carbon and nitrogen elements has been used as an important catalyst support material and photocatalyst, and has been widely used in the field of catalytic selective conversion of organic matter (Nature Materials, 2009, 8 (1): 76; Journal of the American Chemical Society, 2010, 132 (46): 16299). The specific interaction between the nitrogen element rich in the carbon nitride polymer material and the supported metal and the modified electronic state are conducive to the fine dispersion and control of metal nanoparticles, making the carbon nitride polymer material a promising catalyst support material in the current heterogeneous catalysis field.
[0005] However, carbon nitride polymers as catalyst supports also have some disadvantages, such as incomplete thermal polymerization, low crystallinity, and low specific surface area (<10m2). 2 / g), a large number of defects in the structure, high exciton binding energy, insufficient reactive sites, etc., seriously restrict the improvement of catalytic performance and practical application. Therefore, optimizing the thermal polymerization process route, promoting the polymerization reaction to proceed in the forward direction, controllably synthesizing high-crystalline carbon nitride (PHI) with a high degree of polymerization, accelerating charge phase migration and interface transfer, are the keys to improving its catalytic performance. So far, there is no relevant report on the application of high-crystalline carbon nitride supported noble metal palladium catalyst in the dehydrogenation reaction of dipentene. Therefore, the present invention prepares a palladium-supported high-crystalline carbon nitride catalyst with high activity, which is of great significance and use value for the supported catalyst for the production of high value-added dehydrogenation products, cymene. Summary of the invention
[0006] The invention provides a preparation method of palladium-loaded highly crystalline carbon nitride and application of the method in catalytic dehydrogenation of dipentene. The prepared palladium-loaded highly crystalline carbon nitride has high catalytic activity and can be used for catalytic dehydrogenation of dipentene to prepare p-cymene. The catalyst is easy to recover and can be used repeatedly.
[0007] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0008] A preparation method of palladium-supported highly crystalline carbon nitride comprises the following steps: calcining a nitrogen-containing precursor and then mixing it evenly with an alkali metal halide salt, calcining and grinding to obtain a solid powder, and then washing, drying and grinding the obtained solid powder to obtain highly crystalline carbon nitride (PHI); and then loading metal palladium on the highly crystalline carbon nitride by a chemical reduction method to obtain a palladium-supported highly crystalline carbon nitride catalyst (Pd / PHI).
[0009] The above washing is to remove the remaining salt.
[0010] The above-mentioned palladium-loaded highly crystalline carbon nitride uses a nitrogen-containing precursor as a raw material and an alkali metal halide as a molten salt. The nitrogen-containing precursor is first calcined, and then a molten salt method is used to heat treat the highly crystalline carbon nitride (PHI); then metal palladium is loaded thereon by a chemical reduction method to obtain a palladium-loaded highly crystalline carbon nitride catalyst (Pd / PHI). The obtained palladium-loaded highly crystalline carbon nitride catalyst has an ordered crystal structure, nanosheet morphology, and pore structure, and has the advantages of a short charge / mass transfer path, rich reaction sites, and easy functionalization, which can promote charge transfer and mass transfer, and has a nitrogen-rich micro-heterocyclic structure with nitrogen-rich electronic properties, which can effectively anchor palladium nanoparticles, regulate the size and dispersion of palladium nanoparticles, and make the binding force between highly crystalline carbon nitride and palladium nanoparticles stronger. The palladium nanoparticles are small in size, uniformly dispersed, and stable, which improves the catalytic performance of dipentene dehydrogenation. The catalyst is used in the catalytic dehydrogenation of dipentene to prepare p-cymene, and high-quality p-cymene products can be obtained, so it is of great significance for the high-value utilization of terpenes.
[0011] In order to ensure the product quality, the preparation method of palladium-supported highly crystalline carbon nitride is as follows: the nitrogen-containing precursor is calcined and mixed with the alkali metal halide salt in a mass ratio of (6-12):1, and then heated in a muffle furnace or a tube furnace under a nitrogen atmosphere at 1-15°C·min -1 The sample was heated to 500-650°C at a heating rate and kept at a constant temperature for 1-6 hours. The sample was then cooled naturally to room temperature and ultrasonically washed with deionized water for more than two times to remove salt from the sample. The sample was then vacuum dried and ground to obtain a highly crystalline carbon nitride sample named PHI.
[0012] The vacuum drying temperature is preferably 50-60°C.
[0013] The mass ratio of the calcined nitrogen-containing precursor to the alkali metal halide salt is (6-12):1.
[0014] The nitrogen-containing precursor of the present application is at least one of cyanamide, dicyandiamide, melamine, ammonium thiocyanate, thiocyanic acid, thiourea or guanidine thiocyanate; the alkali metal halide salt is at least one of lithium chloride, potassium chloride, zinc chloride, lithium bromide, potassium bromide, sodium bromide and mixed eutectic salts thereof.
[0015] In order to improve the catalytic effect, the nitrogen-containing precursor is melamine; the alkali metal halide salt is preferably a mixture of potassium chloride and lithium chloride in a mass ratio of 1: (0.5-1.5).
[0016] The calcination of the nitrogen-containing precursor of the present application is as follows: placing the nitrogen-containing precursor in a muffle furnace or a tube furnace at 1-15°C·min -1The material is heated to 300-650°C at a heating rate and kept at a constant temperature for 1-6 hours, then naturally cooled to room temperature and ground into powder for later use.
[0017] The specific steps of loading metal palladium on high crystalline carbon nitride by chemical reduction method include: mixing high crystalline carbon nitride, deionized water and palladium chloride-hydrochloric acid solution, and ultrasonically dispersing for 20-30 minutes, oil bathing at 70-80°C for 10-12 hours, and adjusting the pH to 9-12 with sodium hydroxide solution, and then adding sodium borohydride solution for reduction, and Pd 2+ Restore to Pd 0 , and then centrifugally separated, washed with water, washed with ethanol, and dried in vacuo to obtain a Pd / PHI catalyst, wherein the palladium loading is 0.1-20wt%, preferably 2-5wt%; wherein the concentration of palladium chloride in the hydrochloric acid-palladium chloride solution is 0.5-200mmol / L, the concentration of hydrochloric acid is 0.1-3mol / L, and the concentration of the sodium borohydride solution is 0.1-0.25mol / L.
[0018] The vacuum drying temperature is preferably 50-60°C.
[0019] The specific steps of adding sodium borohydride solution for reduction are: after adjusting the pH to 9-12, dripping the sodium borohydride solution, and after the dripping is completed, continuing to react in an oil bath at 70-80° C. for 1-3 hours; this application requires an excess of sodium borohydride.
[0020] In order to further ensure product performance, the mass volume ratio of the above-mentioned highly crystalline carbon nitride to deionized water is 1:50-300 g / mL; the mass volume ratio of the highly crystalline carbon nitride to palladium chloride-hydrochloric acid solution is 1:(3-8); the mass volume ratio of the highly crystalline carbon nitride to sodium borohydride solution is 1:(15-20).
[0021] The palladium-loaded highly crystalline carbon nitride prepared above can be used for catalytic dehydrogenation of dipentene to prepare p-cymene. The specific method is: stir and mix the palladium-loaded highly crystalline carbon nitride catalyst and dipentene in a mass ratio of (0.1-2):1, place in a high-pressure reactor, react for 0.5-15h at 30-300°C and 0.01-10Mpa pressure in an argon atmosphere, and after the reaction is completed, centrifuge to remove the palladium-loaded highly crystalline carbon nitride catalyst to obtain p-cymene.
[0022] In order to improve the product yield, the mass ratio of the palladium-loaded high-crystalline carbon nitride catalyst and dipentene is preferably (0.2-0.5):1; the reaction temperature is preferably 150-240°C, more preferably 215-225°C, the argon pressure is preferably 0.1-3MPa, and the reaction time is preferably 6-8h.
[0023] The technologies not mentioned in the present invention are all referred to the prior art.
[0024] The beneficial effects of the present invention are:
[0025] (1) The crystallinity, degree of polymerization, morphology and molecular structure of the palladium-supported highly crystalline carbon nitride prepared by the present invention can be flexibly adjusted by controlling the types and proportions of the precursors and the molten salt.
[0026] (2) The palladium-loaded highly crystalline carbon nitride catalyst prepared by the present invention has the following characteristics: 1) It has an ordered crystal structure, nanosheet morphology and pore structure, a high surface area, and has the advantages of a short charge / mass transfer path, abundant reaction sites, easy functionalization, and a high specific surface area. 2) It has a nitrogen-rich micro-heterocyclic structure, which makes the binding force between highly crystalline carbon nitride and palladium nanoparticles stronger, and the palladium nanoparticles are small in size and evenly distributed; 3) The catalyst is easy to separate and collect, easy to recycle, and has good stability. 4) The palladium loading is low, the catalytic activity is high, and the selectivity is good.
[0027] (3) The palladium-loaded highly crystalline carbon nitride catalyst provided by the present invention has high catalytic activity and is used for the catalytic dehydrogenation of dipentene to prepare p-cymene. When the theoretical loading amount of palladium nanoparticles is 3 wt.%, the p-cymene content in the product can reach 89.74%, and the dipentene conversion rate and p-cymene selectivity are both close to 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of 3% Pd / PHI prepared in Example 1 of the present invention;
[0029] Figure 2 This is a transmission electron microscope image of 3% Pd / PHI prepared in Example 1 of the present invention;
[0030] Figure 3 This is a transmission electron microscope elemental surface scanning image of 3% Pd / PHI prepared in Example 1 of the present invention;
[0031] Figure 4 This is the X-ray powder diffraction pattern of 3% Pd / PHI prepared in Example 1 of the present invention;
[0032] Figure 5 This is a Fourier transform infrared spectrum of 3% Pd / PHI prepared in Example 1 of the present invention;
[0033] Figure 6 This is the X-ray photoelectron spectrum of 3% Pd / PHI prepared in Example 1 of the present invention; DETAILED DESCRIPTION
[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0035] In the embodiments, the microscopic morphology of the sample is obtained by observation using a Verios G4 UC2 scanning electron microscope of the United States; the microscopic morphology and element distribution of the sample are obtained by means of a ThermoFisher Talos F200X field emission transmission electron microscope of the United States; the composition and crystal structure information of the catalyst are obtained by using a Japanese Rigaku Smartlab X2 X-ray powder diffractometer; the chemical composition and functional group structure information of the catalyst are obtained by using a Nicolet is50 infrared spectrometer of the United States; the elemental composition, element content and chemical state of the material surface are identified by using a ThermoFisher K-Alpha+X-ray photoelectron spectroscopy of the United States; and the content of dipentene series components and para-cymene in industrial dipentene is obtained by using an Agilent Intuvo 9000-7000D2 triple tandem quadrupole gas chromatograph-mass spectrometer of the United States.
[0036] The conversion rate of dipentene and the selectivity of the dehydrogenated product to cymene were calculated according to formula (1) and formula (2), respectively.
[0037] Conversion rate of dipentene / % = (M D1 -M D2 ) / M D1 ×100 (1)
[0038] Selectivity for p-cymene / % = M O / (M D1 -M D2 )×100 (2)
[0039] Where M D1 Indicates the relative mass fraction of dipentene in the raw material; M D2 Represents the relative mass fraction of dipentene in the reaction product; M O It represents the relative mass fraction of p-cymene in the reaction product.
[0040] Example 1
[0041] a) Preparation of highly crystalline carbon nitride (PHI): 8 g of melamine was weighed and heated at 5 °C min -1 The sample was heated to 500°C in a muffle furnace at a heating rate of 100 °C and then kept at a constant temperature for 4 h. The sample was cooled to room temperature naturally and ground into powder for later use. 600 mg of the ground powder sample was weighed and mixed with 3.3 g of potassium chloride and 2.7 g of lithium chloride. The sample was placed in a tube furnace under a nitrogen atmosphere at 5 °C·min -1 The sample was heated to 550℃ at a rate of 1000℃ and kept at this temperature for 4 hours, cooled to room temperature naturally, and ground into powder. Water was added for ultrasonic dispersion, and the sample was filtered three times to remove potassium chloride and lithium chloride from the sample. The sample was vacuum dried at 60℃, and then the sample was collected and ground into powder, which was named PHI.
[0042] b) Preparation of palladium-supported high-crystalline carbon nitride (Pd / PHI) catalyst: 25 mg of PdCl2, 2 mL of 2 mol / L hydrochloric acid (HCl mass concentration of 0.73 wt%) and 40 mL of water were added to a flask, 0.5 g of PHI powder was weighed, and after ultrasonic-assisted dispersion for 30 min, refluxed in an oil bath at 80°C, and immersed for 12 h under magnetic stirring. Then, NaOH solution was added to adjust the pH to 10, and 8 mL of 0.18 mol / L NaBH4 solution was slowly added (12 drops / min). After the addition was completed, the reaction was continued to be stirred in an oil bath at 80°C for 2 h, and centrifuged. The resulting precipitate was washed with water and ethanol in turn, and then dried in vacuum at 60°C to obtain 3% Pd / PHI, wherein the theoretical loading of Pd was 3 wt%.
[0043] The SEM image of 3% Pd / PHI prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that the Pd / PHI sample shows stacked nanosheet morphology and stacked pore structure.
[0044] The transmission electron microscopy image of 3% Pd / PHI prepared in this example is as follows: Figure 2 As shown in the figure, it can be seen that PHI has the morphology of nanosheets. The particle size of palladium nanoparticles is 3-4nm and is evenly dispersed on the PHI nanosheets.
[0045] The TEM elemental surface scanning image of 3% Pd / PHI prepared in this example is shown in Figure 3 As shown in the figure, it can be seen that the C, N, K, and Pd elements of Pd / PHI are evenly distributed, indicating that the palladium nanoparticles are evenly dispersed on PHI.
[0046] The X-ray powder diffraction pattern of 3% Pd / PHI prepared in this example is as follows: Figure 4As shown in the figure, it can be found that the 7% Pd / PHI (prepared in Example 8) catalyst has two obvious diffraction peaks at 8.1° and 27.5°, which are attributed to the (100) and (002) crystal planes of graphite phase carbon nitride. The former peak is caused by the periodic repetition of the heptazine unit in the plane, and the latter diffraction peak is attributed to the layered stacking of the heptazine structure similar to graphite. It is confirmed that the prepared Pd / PHI contains heptazine-based graphite phase carbon nitride. No obvious diffraction peaks of KCl and LiCl were observed in the X-ray powder diffraction pattern, indicating that KCl and LiCl have been completely removed during the water washing process. The main peak with the largest diffraction intensity of the 7% Pd / PHI sample is narrow at half-height width, indicating that the Pd / PHI sample has an ordered crystal structure with high crystallinity and polymerization degree. This is because the nitrogen-containing precursor after pre-calcination is reconstructed in the high-temperature solvent of the molten salt to generate highly crystalline carbon nitride. By zooming in on the characteristic peaks of metallic Pd in the X-ray powder diffraction pattern, we can see that 2θ=39.8° and 46.0° correspond to the (111) plane and (200) plane of Pd (PDF#88-2335), respectively, which provides a basis for the formation of Pd nanoparticles.
[0047] The Fourier transform infrared spectrum of 3% Pd / PHI prepared in this example is shown in Figure 5 As shown, at 810cm -1 There is a fingerprint vibration peak of the oxazine ring at 1200-1700cm -1 The infrared absorption peak is caused by the stretching vibration of the heptazine ring. -1 The absorption peak at 3000-3500cm is attributed to the vibration of cyano group, which is mainly caused by the loss of amino group on the sample surface and the decomposition of some heptazine rings. -1 There is a broad absorption peak, which is mainly caused by the vibration of the surface amino group. This figure shows that Pd / PHI contains heptazine-structured carbon nitride.
[0048] The X-ray photoelectron spectrum of 3% Pd / PHI prepared in this example is as follows: Figure 6 As shown. From the full range spectrum, the peaks of five elements, C, N, K, O, and Pd, can be observed. In addition, C1 S , N 1s, K 2p, Pd 3d, Li 1s, Cl 2p, O1s high-resolution spectra. The peak of C 1s high-resolution spectrum can be decomposed into three peaks, located at 284.8, 286.4 and 288.3 eV, respectively, of which the peak at 288.3 eV is the strongest. The peaks at 286.4 and 288.3 eV are mainly from the sp 2Hybridization is the main structure of carbon nitride polymer. The peak at 284.8 eV is generally attributed to impurity carbon. The peak of N 1s can be decomposed into four peaks, among which the peak at 398.8 eV is attributed to the sp 2 Hybridization (CN=C), the peak at 400.5eV is attributed to the ternary nitrogen N-(C)3 in the heptazine ring. These two structures of carbon atoms and nitrogen atoms are the main structures of the carbon nitride framework. The peak at 401.3eV indicates that the structure contains amino groups (CNH), which mainly exist on the surface of the sample. The peak at 404.1eV may be caused by the charging effect or the positive charge localization effect. Two peaks attributed to the K 2p orbital were also observed in the spectrum, located at 293.1eV and 295.9eV, respectively, indicating the presence of K ions in the synthesized highly crystalline carbon nitride. However, no peaks of Li and Cl were observed in the high-resolution spectrum, indicating that these elements have been removed after washing with a large amount of deionized water. The structure contains cyano groups, which is consistent with the results of infrared spectroscopy. The Pd 3d spectrum consists of two asymmetric peaks assigned to the core energy levels of Pd 3d5 / 2 and Pd 3d3 / 2, and two double peaks can be used for fitting. The peaks around 336.0 and 341.4 eV are attributed to metallic Pd 0 , while the peaks around 338.2 and 343.3 eV correspond to Pd 2+ 3% Pd / PHI has a nitrogen-rich micro-heterocyclic structure. The interaction between the nitrogen element contained in it and the loaded Pd metal helps to finely disperse and control the size of Pd nanoparticles, and the negative charge presented by its nitrogen position increases the electron density of Pd nanoparticles to a certain extent.
[0049] c) Catalytic dehydrogenation of dipentene to prepare p-cymene: Add catalyst and 5g industrial dipentene into a high-pressure reactor, stir, introduce argon and evacuate to drive out the air inside, and then carry out the reaction of dipentene dehydrogenation to prepare p-cymene. The reaction conditions are: catalyst is 3% Pd / PHI, catalyst mass is 0.1g, temperature is 220°C, argon pressure is 0.5MPa, and reaction time is 6h. After the reaction is completed, centrifuge (centrifuge at a speed of 8000 rpm for 5 minutes) to separate, take the supernatant, dilute it 100 times with methanol, and test it using gas chromatography-mass spectrometry. The conversion rate of dipentene and the selectivity and content of p-cymene are shown in Table 3.
[0050] Example 2
[0051] The catalyst synthesis steps are the same as those in Example 1. The conditions for the catalytic dehydrogenation of dipentene are: 3% Pd / PHI catalyst, 0.1 g catalyst mass, 150° C., and 6 h reaction time. The rest are the same as those in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0052] Example 3
[0053] The catalyst synthesis steps are the same as those in Example 1. The conditions for the catalytic dehydrogenation of dipentene are: 3% Pd / PHI as catalyst, 0.1 g as catalyst mass, 180° C. as temperature, 6 h as reaction time, and the rest are as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0054] Example 4
[0055] The catalyst synthesis steps are the same as those in Example 1. The conditions for the catalytic dehydrogenation of dipentene are: 3% Pd / PHI catalyst, 0.1 g catalyst mass, 200°C temperature, 6 h reaction time, and the rest are as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0056] Example 5
[0057] The catalyst synthesis steps are the same as those in Example 1. The conditions for the catalytic dehydrogenation of dipentene are: 3% Pd / PHI catalyst, 0.1 g catalyst mass, 240°C temperature, 6 h reaction time, and the rest are as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0058] Example 6
[0059] During the catalyst synthesis, the difference from Example 1 was that the amount of PdCl2 added was 8.3 mg, and the rest was completely referred to Example 1, to obtain a catalyst of 1% Pd / PHI, that is, the theoretical loading amount of Pd was 1 wt%. The conditions for the catalytic dehydrogenation of dipentene were: the catalyst was 1% Pd / PHI, the catalyst mass was 0.1 g, the temperature was 220° C., the reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0060] Example 7
[0061] During the catalyst synthesis, the difference from Example 1 was that the amount of PdCl2 added was 42 mg, and the rest was completely referred to Example 1, to obtain a catalyst 5% Pd / PHI, that is, the theoretical loading of Pd was 5wt%. The conditions for the catalytic dehydrogenation of dipentene were: the catalyst was 5% Pd / PHI, the catalyst mass was 0.1 g, the temperature was 220° C., the reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0062] Example 8
[0063] During the catalyst synthesis, the difference from Example 1 was that the amount of PdCl2 added was 58 mg, and the rest was completely referred to Example 1, to obtain a catalyst of 7% Pd / PHI, that is, the theoretical loading of Pd was 7wt%. The conditions for the catalytic dehydrogenation of dipentene were: the catalyst was 7% Pd / PHI, the catalyst mass was 0.1 g, the temperature was 220°C, the reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0064] Example 9
[0065] The 3% Pd / PHI after the reaction in Example 1 was recovered as follows: the precipitate obtained by centrifugation after the reaction was completed was washed with water and ethanol in sequence, and then dried in vacuum at 60° C. to obtain 3% Pd / PHI-1 which could be reused once.
[0066] 3% Pd / PHI-1 was used again for the catalytic dehydrogenation of dipentene, and the conditions were: catalyst was 3% Pd / PHI-1, catalyst mass was 0.1 g, temperature was 220° C., reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0067] Example 10
[0068] The 3% Pd / PHI-1 after the reaction in Example 9 was recovered again, and the steps were as follows: after the reaction was completed, centrifugation was performed (at a speed of 8000 rpm for 5 minutes), and the obtained precipitate was washed with water and ethanol in turn, and then vacuum dried at 60°C to obtain 3% Pd / PHI-2 which was reused twice.
[0069] 3% Pd / PHI-2 was used again for the catalytic dehydrogenation of dipentene, under the following conditions: catalyst was 3% Pd / PHI-2, catalyst mass was 0.1 g, temperature was 220° C., reaction time was 6 h, and the rest was as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0070] Comparative Example 1
[0071] The synthesis steps of highly crystalline carbon nitride (PHI) are the same as those in Example 1. The experimental steps of palladium loading were removed, and PHI was directly used for the catalytic dehydrogenation reaction of dipentene under the following conditions: the catalyst was PHI, the catalyst mass was 0.1 g, the temperature was 220° C., the reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0072] Comparative Example 2
[0073] Preparation of low crystalline carbon nitride (CNM): 8 g of melamine was weighed and heated at 5 °C min-1 The reaction mixture was heated to 500°C in a muffle furnace at a heating rate of 1000 °C and kept at a constant temperature for 4 hours, then cooled to room temperature naturally and ground into powder to obtain low crystalline carbon nitride (CNM). CNM was directly used for catalytic dehydrogenation of dipentene under the following conditions: CNM as catalyst, 0.1 g of catalyst mass, temperature of 220°C, reaction time of 6 h, and the rest were referred to Example 1. The conversion rate of dipentene and the selectivity and content of cymene are shown in Table 3.
[0074] Comparative Example 3
[0075] Preparation of low crystalline carbon nitride (CNM): 8 g of melamine was weighed and heated at 5 °C min -1 The temperature was raised to 500°C in a muffle furnace at a rate of 100°C and then kept constant for 4 hours, cooled naturally to room temperature, and ground into powder to obtain low crystalline carbon nitride (CNM). Low crystalline carbon nitride (CNM) was directly loaded with palladium. The experimental steps of palladium loading were the same as those in Example 1, and Pd-loaded low crystalline carbon nitride (3% Pd / CNM) with a theoretical Pd loading of 3wt% was obtained. The reaction conditions for the catalytic dehydrogenation of dipentene were: the catalyst was 3% Pd / CNM, the catalyst mass was 0.1g, the temperature was 220°C, the reaction time was 6h, and the rest were referred to Example 1. The conversion rate of dipentene and the selectivity and content of cymene are shown in Table 3.
[0076] Comparative Example 4
[0077] The conditions for the catalytic dehydrogenation of dipentene are as follows: the catalyst is commercial 10% palladium carbon (containing 55% water, purchased from Biter Pharmaceuticals), the catalyst mass is 0.1 g, the temperature is 220° C., the reaction time is 6 h, and the rest are as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0078] Comparative Example 5
[0079] The commercial 10% palladium carbon after the reaction in Comparative Example 4 was recovered, and centrifuged (at 8000 rpm for 10 minutes). The obtained precipitate was washed with water and ethanol in turn, and then vacuum dried at 60°C to obtain 10% Pd / C-1 which was reused once. Pd / C-1 was used again for the catalytic dehydrogenation of dipentene under the following conditions: the catalyst was 10% Pd / C-1, the catalyst mass was 0.1 g, the temperature was 220°C, the reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0080] Comparative Example 6
[0081] The commercial 10% Pd / C-1 after the reaction in Comparative Example 5 was recovered, centrifuged (at 8000 rpm for 10 minutes), and the obtained precipitate was washed with water and ethanol in turn, and then vacuum dried at 60°C to obtain 10% Pd / C-2 which was reused twice. Pd / C-2 was used again for the catalytic dehydrogenation of dipentene under the following conditions: the catalyst was 10% Pd / C-2, the catalyst mass was 0.1 g, the temperature was 220°C, the reaction time was 6 h, and the rest was referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0082] Comparative Example 7
[0083] The conditions for the catalytic dehydrogenation of dipentene are as follows: the catalyst is H-ZSM-5 molecular sieve (Si / Al=30), the catalyst mass is 0.1 g, the temperature is 220° C., the reaction time is 6 h, and the rest are as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0084] Comparative Example 8
[0085] The conditions for the catalytic dehydrogenation of dipentene are as follows: the catalyst is commercial Raney Ni (purchased from Ron Pharmaceuticals), the catalyst mass is 0.1 g, the temperature is 220° C., the reaction time is 6 h, and the rest are as in Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0086] Comparative Example 9
[0087] The conditions for the catalytic dehydrogenation of dipentene are as follows: the catalyst is commercial palladium carbon + Raney nickel (mixed in a mass ratio of 1:1), the catalyst mass is 0.1 g, the temperature is 220° C., the reaction time is 6 h, and the rest are referred to Example 1. The dipentene conversion rate and the selectivity and content of p-cymene are shown in Table 3.
[0088] Table 1 Gas chromatography-mass spectrometry analysis results of dipentene raw materials used in each example
[0089]
[0090] Table 1 shows the results of gas chromatography-mass spectrometry analysis of the industrial dipentene raw materials used in each case. The sum of the mass fractions of the four components belonging to the dipentene series in the industrial dipentene raw materials, namely limonene, terpinene, α-terpinene and γ-terpinene, is 78.67%, and it also contains 10.04% of p-cymene. Other impurities mainly include a small amount of carene, fenchol, isoborneol and borneol.
[0091] Table 2 Gas chromatography-mass spectrometry analysis results of industrial dipentene dehydrogenation products obtained in Example 1
[0092]
[0093] Table 2 shows the results of gas chromatography-mass spectrometry analysis of the industrial dipentene dehydrogenation product obtained in Example 1 of the present invention. Under the condition of 220°C, the dehydrogenation product of p-cymene in the 3% Pd / PHI catalyzed dipentene dehydrogenation reaction mainly contains 89.74% of p-cymene, which basically reaches the theoretical value, and also contains a small amount of cis- or trans-p-cymene. Alkane 10.21%.
[0094] Table 3 Dipentene conversion rate and para-cymene selectivity and content in each case
[0095]
[0096]
[0097] Table 3 shows the conversion rate of dipentene and the selectivity and content of p-cymene of the catalysts of the embodiments of the present invention and the comparative examples. First, the effect of reaction temperature on the synthesis of p-cymene from dipentene by 3% Pd / PHI was investigated. When the reaction temperature was increased from 150°C to 220°C, the content of p-cymene in the dipentene dehydrogenation reaction catalyzed by 3% Pd / PHI also increased. This is because the reaction of dipentene dehydrogenation to prepare p-cymene is an endothermic reaction with a relatively significant thermal effect. Increasing the reaction temperature within a suitable temperature range is conducive to the formation of p-cymene. In the comparative experiment of different reaction temperatures, when the temperature is 220°C, 3% Pd / PHI has the best catalytic effect. The content of p-cymene in the dipentene dehydrogenation product catalyzed by 3% Pd / PHI is the highest (reaching 89.74%), and its dipentene conversion rate and p-cymene selectivity are both close to 100%. However, when the temperature exceeds 220°C, such as 240°C, the content of p-cymene in the product of 3% Pd / PHI catalysis product is slightly reduced. Therefore, 220°C is preferably the reaction temperature for preparing p-cymene by dehydrogenation of dipentene.
[0098] Secondly, the effect of Pd loading on the catalytic activity of Pd / PHI was studied. Among the samples with different Pd contents, 3% Pd / PHI catalyzed the highest content of dipentene dehydrogenation to produce p-cymene. However, reducing the Pd loading to 1% or increasing it to 7% slightly reduced the content of p-cymene.
[0099] Again, the stability of the Pd / PHI catalyst was investigated. The 3% Pd / PHI sample after the reaction was recovered and reused twice, and it was found that the content of p-cymene in its product did not significantly decrease. However, when commercial palladium carbon that was reused twice was used as a catalyst, the content of p-cymene in its product was significantly reduced. This proves that the Pd / PHI catalyst has good catalytic activity stability.
[0100] Finally, the catalytic activities of different types of catalysts were compared. The catalytic performance of 3% Pd / PHI is higher than that of high-crystalline carbon nitride PHI without Pd loading, low-crystalline bulk carbon nitride, and 3% palladium-loaded bulk carbon nitride, and is significantly better than commercial Pd / C, H-ZSM-5 molecular sieve (Si / Al=30), Raney Ni, and a mixture of commercial Pd / C and Raney Ni (mixed in a mass ratio of 1:1). The above examples and comparative examples fully demonstrate that the palladium-loaded high-crystalline carbon nitride catalyst of the present application has good catalytic effect and stability in the catalytic dehydrogenation of dipentene to prepare para-cymene, and significantly reduces the palladium loading and reduces the cost.
Claims
1. An application of palladium-supported highly crystalline carbon nitride, characterized in that: Used for catalytic dehydrogenation of dipentene to prepare p-cymene; the method for catalytic dehydrogenation of dipentene to prepare p-cymene is: stir and mix a palladium-supported high-crystalline carbon nitride catalyst and dipentene in a mass ratio of (0.1-2):1, place in a high-pressure reactor, react for 0.5-15 h at 30-300°C and 0.01-10 MPa pressure argon atmosphere, and after the reaction, centrifuge to remove the palladium-supported high-crystalline carbon nitride catalyst to obtain p-cymene; The preparation method of palladium-loaded highly crystalline carbon nitride is as follows: a nitrogen-containing precursor is calcined and then mixed evenly with an alkali metal halide salt, and solid powder is obtained by calcination and grinding. The obtained solid powder is then washed, dried, and ground to obtain highly crystalline carbon nitride; and metal palladium is loaded on the highly crystalline carbon nitride by a chemical reduction method to obtain a palladium-loaded highly crystalline carbon nitride catalyst.
2. The use according to claim 1, characterized in that: The mass ratio of the palladium-supported high-crystalline carbon nitride catalyst to dipentene is (0.2-0.5):1; the reaction temperature is 150-240°C, the argon pressure is 0.1-3 MPa, and the reaction time is 6-8 h.
3. The use according to claim 1 or 2, characterized in that: The preparation method of palladium-supported highly crystalline carbon nitride is as follows: a nitrogen-containing precursor is calcined and mixed with an alkali metal halide salt in a mass ratio of (6-12):1, and heated in a muffle furnace or a tube furnace at 1-15°C·min under a nitrogen atmosphere. -1 The sample was heated to 500-650°C at a heating rate and kept at a constant temperature for 1-6 hours. The sample was then naturally cooled to room temperature and ultrasonically washed with deionized water for more than two times to remove salt from the sample. The sample was then vacuum dried and ground to obtain a highly crystalline carbon nitride sample.
4. The use according to claim 1 or 2, characterized in that: The nitrogen-containing precursor is at least one of cyanamide, dicyandiamide, melamine, ammonium thiocyanate, thiocyanic acid, thiourea or guanidine thiocyanate; the alkali metal halide salt is at least one of lithium chloride, potassium chloride, lithium bromide, potassium bromide, sodium bromide and mixed eutectic salts thereof.
5. The use according to claim 4, characterized in that: The nitrogen-containing precursor is melamine; the alkali metal halide salt is a mixture of potassium chloride and lithium chloride in a mass ratio of 1:(0.5-1.5).
6. The use according to claim 1 or 2, characterized in that: The calcination of the nitrogen-containing precursor is as follows: the nitrogen-containing precursor is placed in a muffle furnace or a tube furnace at 1-15°C·min -1 The material is heated to 300-650°C at a heating rate and kept at a constant temperature for 1-6 hours, then naturally cooled to room temperature and ground into powder for later use.
7. The use according to claim 1 or 2, characterized in that: The specific steps of loading metal palladium on high crystalline carbon nitride by chemical reduction method include: mixing high crystalline carbon nitride, deionized water and palladium chloride-hydrochloric acid solution, ultrasonically dispersing for 20-30 minutes, oil bathing at 70-80°C for 10-12 hours, adjusting the pH value to 9-12 with sodium hydroxide solution, adding sodium borohydride solution for reduction, and then centrifugation, water washing, ethanol washing, and vacuum drying to obtain Pd / PHI catalyst, wherein the loading amount of palladium is 0.1-20 wt%; wherein the concentration of palladium chloride in the hydrochloric acid-palladium chloride solution is 0.5-200 mmol / L, the concentration of hydrochloric acid is 0.1-3 mol / L, and the concentration of sodium borohydride solution is 0.1-0.25 mol / L.
8. The use according to claim 7, characterized in that: After adjusting the pH to 9-12, sodium borohydride solution was added dropwise. After the addition was completed, the reaction was continued in an oil bath at 70-80° C. for 1-3 hours.
9. The use according to claim 7, characterized in that: The mass volume ratio of highly crystalline carbon nitride to deionized water is 1:50-300 g / mL.
Citation Information
Patent Citations
Pd / crystallized carbon nitride heterojunction photocatalyst, preparation method thereof and application of photocatalytic Ullmann coupling reaction
CN108452821A
Preparation method of precious metal nanoparticle-loaded 2D bismuth vanadate@PDA core-shell structure composite material
CN113877632A